Increased risk of phthalates exposure for recurrent pregnancy loss in reproductive-aged women. (October 2018) - Liao, Kai-Wei; Kuo, Pao-Lin; Huang, Han-Bin; Chang, Jung-Wei; Chiang, Hung-Che; Huang, Po-Chin
Abstract: Recurrent pregnancy loss (RPL) is the termination of pregnancies, usually before 20 weeks of gestation, and is defined as the loss of two or more pregnancies. In Taiwan, after 2011 di-2-ethylhexyl phthalate (DEHP) exposure episode, more reproductive-aged women still expose to high levels of DEHP and di-butyl phthalate (DBP) than have women of other age groups. Phthalates might be involved in the RPL pathogenesis. This study assessed the association of phthalate exposure with RPL risk in reproductive-aged Taiwanese women. This study recruited 103 patients diagnosed by a physician with RPL of unknown etiology and 76 controls from the Department of Obstetrics and Gynecology at a medical center in southern Taiwan between August 2013 and August 2017. Urine samples were analyzed for 11 phthalate metabolites through liquid chromatography–tandem mass spectrometry; subsequently, principal component analysis (PCA) and hierarchical clustering analysis were performed to determine the main sources of phthalate exposure. Finally, multivariate logistic regression was used to determine the RPL risk. The creatinine-unadjusted median levels of mono-iso-butyl phthalate (MiBP), mono- n -butyl phthalate (MnBP), mono-(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), and mono-(2-ethyl-5-carboxypentyl) phthalate (MECPP) in RPL/control were 9.8/5.3, 27.2/13.1, 11.4/8.1, and 12.9/9.5 ng/mL, respectively; furthermore, ΣDBPm and ΣDEHPm in RPL/control were 0.18/0.10 and 0.15/0.12 nmol/mL, respectively. PCA revealed three primary components of phthalate exposure: diethyl phthalates (DEP), DEHP, and DBP. Plastic food container use and medication were identified as the main phthalate exposure sources. After adjustment for potential confounding factors (urinary creatinine, age, age at menarche, education, and plastic food container use), we found that the urinary level of ΣDBPm was significantly associated with elevated risk for RPL (OR = 2.85, p = 0.045). Our findings supported the hypothesis that exposure to phthalates increases RPL risk. The development of a strategy to reduce phthalate exposure among reproductive-aged women should be emphasized. Graphical abstract: Highlights: A case-control study assessed urinary phthalates exposure and the risk of recurrent pregnancy loss (RPL). Principal component analysis indicated that primary urinary phthalate metabolites were MEP, MiBP, and DEHP oxidative metabolites. Significantly increased risk of urinary ΣDBPm levels in patients with RPL was observed. Plastic food container use and medication are potential sources of phthalate exposure. Our findings suggested that phthalate exposure should be considered a risk factor for patients with RPL, especially for DBP. Abstract : Phthalates exposure increase the risk of recurrent pregnancy loss.